Teor de macronutrientes na parte aérea e sementes de plantas de alface em função de doses de composto orgânico com e sem adição de fósforo ao solo - de Quadros, Barbara Rodrigues [UNESP]; Magro, Felipe Oliveira [UNESP]; Correa, Carla Veronica [UNESP]; Inacio Cardoso, Antonio Ismael [UNESP] (Universidade Estadual de Londrina (UEL), 2011)
This study was conducted in the Sao Manuel experimental Farm, in Sao Manuel-SP, which belongs to the Faculdade de Ciencias Agronomicas (FCA) of the Universidade Estadual Paulista (UNESP), Botucatu/SP Campus, in order to evaluate the influence of organic compost doses, with and without added phosphorus to the soil, on the levels of macronutrients in plants and seeds of the lettuce cultivar Veronica. The experimental design was randomized blocks with ten treatments (0, 20, 40, 60, 80 Mg ha(-1) of organic compost, with and without 400 kg ha-1 P 2 0 5 added to the soil) and four replicates. The content of macronutrients in plants and seeds was evaluated. The data were submitted to analysis of variance and regression. The decreaning order of macronutrient content in plants was potassium > calcium > nitrogen > magnesium > phosphorus > sulfur and in seeds it was nitrogen > phosphorus > potassium > calcium > magnesium > sulfur. The nitrogen content in seeds, was about three and a half times higher than in plants, the sulfur was one and half times higher, while phosphorus content was approximately five times higher.
Nutrients content in lettuce plants and seeds in function of organic compost levels, with and without added phosphorus to the soil
Keywords: Lactuca sativa; phosphorus fertilization and organic fertilization